Equation of state and transport properties of metals in warm dense matter regime. Issue 2 (28th December 2017) - Khomkin, A.L.; Shumikhin, A.S.
Abstract : The equation of state, composition, and electrical conductivity are calculated for the supercritical ionized fluid of aluminium. For calculation, we used the previously proposed chemical plasma model called "3+"‐component. The model includes atoms, immersed in jellium, and thermal electrons and ions. Part of the bound states electron density is referred to as jellium. The density of electron jellium increases with the compression of atomic gas and does not depend on temperature directly. The emergence of jellium can be termed the process of ionization in the full sense of the word. The conductivity of dense vapours is determined by the sum of the conductivity of the thermal electrons, calculated according to the Frost formula, and the conductivity of jellium, calculated according to the Regel–Ioffe formula. At compression, the electrical conductivity passes through the minimum from the conductivity of thermal electrons to the conductivity of electrons of jellium accordingly. Calculations of the equation of state and the electrical conductivity of supercritical metal vapours agree well with physical and numerical experimental data.